2021
DOI: 10.2147/rru.s325929
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Single-Blinded Clinical Trial Evaluating the Effect of Extracorporeal Shockwave Treatment (ESWT) as Add-On Therapy to Vacuum Erectile Device on Peyronie’s Disease

Abstract: The aim of this study was to investigate whether ESWT with a higher energy as an add-on therapy to vacuum-pump followed by manipulation exercises could reduce the penile curvature, pain and improve IIEF-5 score. Materials and Methods: Men aged >18 and <80 years and diagnosed with PD in stable phase with no history of penile surgery or previous ESWT treatment were eligible to participate. They were randomised to either active ESWT (n = 16) or sham ESWT (n = 16). Both groups were treated once a week for five wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The treatment and control groups consisted of 16 participants, who received either ESWT or placebo, and were instructed to use the aforementioned form of PTT. No difference has been shown in terms of mean penile curvature, EF, or pain 88 …”
Section: Other Non‐invasive Methods Of Treatmentmentioning
confidence: 85%
See 2 more Smart Citations
“…The treatment and control groups consisted of 16 participants, who received either ESWT or placebo, and were instructed to use the aforementioned form of PTT. No difference has been shown in terms of mean penile curvature, EF, or pain 88 …”
Section: Other Non‐invasive Methods Of Treatmentmentioning
confidence: 85%
“…Two more prospective studies evaluated the combined effect of combining PTT and CCH or extracorporeal shockwave therapy (ESWT), and are described in the respective chapters of the review. 40,88 Compared with other conservative treatment methods, studies investigating PTT also reported a significant increase in stretched penile length (SPL). However an improvement of curvature was not shown in a retrospective trial by Ziegenmann et al 89 Several prospective studies reported positive outcomes with PTT, although the quality of the evidence is limited due to the lack of blinding.…”
Section: Penile Traction Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…[ 13 ] Mortensen et al studied the combined treatment of vacuum pump and ESWT, and finally recognized that ESWT is a non-invasive treatment with less side effects, but has no significant effect on the improvement of major symptoms. [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…49% of patients required subsequent surgical correction [85]. In a recent clinical study examining the effect of extracorporeal shock wave treatment, no additional significant results were observed from an applied combination with PP [86].…”
Section: Therapeutical Ultrasoundmentioning
confidence: 99%